2013
DOI: 10.1002/app.39921
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and characterization of thermoplastic antistatic polyurethane synthesized by in situ polymerization

Abstract: Antistatic polyurethane (APU) is prepared by in situ polymerization of polyester glycol (PEL), 4,4 0 -diphenylmethane diisocyanate (MDI), 1,4-butanediol (BDO), and antistatic agent (AA) formed by dissolving sodium salts in polyethylene glycol (PEG). Comprehensive properties of the APU are investigated by the FT-IR, mechanical characterization, surface resistivity measurement, relative humidity (RH) study, and TGA, respectively. It is found that the surface resistivity of the APU can be effectively reduced to 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…Therefore, this problem of PUs has become the focus of many researches; and some antistatic or conductive PUs have been studied for decades [3]. Plenty of studies have reported that existing methods to avoid static electricity in polymers commonly include two ways: one is adding antistatic agent and mixing conductive fillers such as carbon black [4], graphite [5], carbon nanotubes [6], as well as inorganic salt [7]; the other one is the surface modification of materials such as surface radiation and spreading conductive coating [8]. Both of them are often adopted to reduce the surface resistivity of PUs.…”
Section: Xcmmentioning
confidence: 99%
“…Therefore, this problem of PUs has become the focus of many researches; and some antistatic or conductive PUs have been studied for decades [3]. Plenty of studies have reported that existing methods to avoid static electricity in polymers commonly include two ways: one is adding antistatic agent and mixing conductive fillers such as carbon black [4], graphite [5], carbon nanotubes [6], as well as inorganic salt [7]; the other one is the surface modification of materials such as surface radiation and spreading conductive coating [8]. Both of them are often adopted to reduce the surface resistivity of PUs.…”
Section: Xcmmentioning
confidence: 99%
“…More recently an antistatic polyurethane was prepared in situ using a polymer of polyester glycol containing antistatic agent (135). Nonmigrating antistatic agents were investigated for coating electric cables (136).…”
Section: Antistatic Agents For Plasticsmentioning
confidence: 99%
“…The popularity of PU elastomers actually derives from the fact that their functional properties can be easily tuned by the choice of reaction components, preparation and processing conditions. The variability of the composition of macrodiols: difference in length and mainly in the constitution (based on polyether, polyester, polycarbonate, polybutadiene and their combinations); chemical nature of diisocyanates (aromatic, aliphatic or cycloaliphatic), and a wide choice of chain extenders (mainly short diols, as butane‐1,4‐diol), together with the possibility to modify the preparation procedure offer an almost infinite variety in end‐use (often unique) properties.…”
Section: Introductionmentioning
confidence: 99%
“…It means that, in addition to the reproducible preparation protocol, the characterization of prepared materials and the study of their macroscopic and microscopic properties and of their structure both on large and on the nanometer scales have to be performed in great detail. The differential scanning calorimetry (DSC), dynamic mechanical thermal analysis (DMTA), thermogravimetry analysis (TGA), and tensile characterization are the most important methods of material characterization that have been widely used for studying broad diversity of macroscopic functional properties in PUE systems.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation